Terapia de reposição da enzima alfa-L-iduronidase recombinante em pacientes portadores de mucopolissacaridose do tipo I: análise de glicosaminoglicanos urinários e correlações clínicas - Braghiroli, Patricia Santos [UNIFESP] (2009)
Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disease caused by deficiency of -L-iduronidase, which cleaves terminal iduronic acid residues of glycosaminoglycans (GAGs), heparan sulphate (HS) and dermatan sulphate (DS). Impairment of degradation leads to its accumulation and increased urinary excretion, with a wide spectrum of clinical severity. The aim of this work was to evaluate the effects of periodic enzyme replacement therapy (ERT) with recombinant -L-iduronidase in MPS I patients. Three patients were weekly treated with Laronidase (Aldurazyme®), 0,58 mg/kg intravenously. Clinical evaluation and analysis of urinary GAGs were done before and after ERT. Two clinically severe Hurler and one mild Hurler-Scheie patients were enrolled in this study. After 19 to 22 months of treatment, the effects observed herein are in accordance with previous data, showing efficacy of ERT on reducing hepatosplenomegaly and clinical improvements, without changing mental impairment of the Hurler patients. Remarkably were the findings of decreasing DS excretion for all patients, the value not returning to the initial baseline. One exception was for the Hurler- Scheie patient who presented a peak of higher values after 11 months of infusion after interruption of treatment, followed by important decrease after return to ERT. Noteworthy was the case of this same patient, whose DS decreased, whereas a progressive increase of CS was observed. Although CS is not present in MPS I urine, it is the predominant GAG in normal individuals. ERT may not be a cure for these diseases and improvement cannot reach all the tissues and affected organs, but represents a safe alternative choice of treatment while gene therapy is not available for humans.